An Angle-Dependent Bias Compensation Method for Hemispherical Resonator Gyro Inertial Navigation Systems - Liu, Chao; Lou, Qixin; Li, Ding; Li, Huiping; Lan, Tian; Wu, Yutao; Meng, Hongjie; Li, Jingyu; Xia, Tao; Yu, Xudong (Sensors (Basel, Switzerland), 2025)
In the whole-angle mode of a hemispherical resonator gyro (HRG), the external input rotation angle is obtained by detecting the standing-wave rotation angle through electrodes. Due to this operational principle and manufacturing constraints of HRGs, the gyro output in an HRG inertial navigation system exhibits angle-dependent errors that are highly sensitive to temperature variations. To address this issue, this paper proposes a system-level calibration scheme to characterize and compensate for these correlated errors. Angle-dependent bias models were established through multi-temperature point experiments. A Kalman filter was subsequently designed, and a calibration path satisfying observability requirements was developed. System-level calibration experiments were conducted to determine and compensate for the identified errors. Finally, navigation experiments demonstrated the effectiveness of the proposed method, showing that the navigation accuracy of the HRG inertial navigation system was improved by up to 94.35%.